Livestock Farming in Relations between Urban Districts and the Mountains – The Case Of Grenoble - Jean-Baptiste Grison; Bernard Pecqueur; Claire Delfosse; Pierre Le Gall (Revue de Géographie Alpine)
This article looks at the way in which the agri-food sectors of the peri-urban mountains are linked to the metropolis, using the case of Grenoble and the massifs that surround the city. First, a historical reading highlights the evolution, over time, of the relationship between livestock farming and the city, with the transition from a context of pressure on the supply of fresh produce (particularly milk) to a gradual de-territorialization of the sectors and, more recently, changes that increasingly favor local sectors. This recomposition is analyzed, in the second part, by observing the roles of actors at different levels of the life of the products, from the farmer to the consumer. We show that farmers in the peri-urban mountains have considerably changed their production models to adapt to the new demands of the nearby city. In the third part, we propose a geographical reading of these city-mountain relations through livestock farming, in which we show that the massifs surrounding Grenoble do not all have the same relationship with the city. In conclusion, we argue that the relationship between mountain livestock and the metropolis is part of interterritoriality, but also that it allows the emergence of specific agricultural models and agri-food circuits.